Evaluation of a computer-assisted monitoring (CAMO) project: Some measurement issues - Gould, Larry A. (American journal of criminal justice, 1995)
This article investigates the effect of Computer Assisted Monitoring of Offenders (CAMO) on probation outcome. In a comparison sample, the effect of CAMO treatment is compared to the effect of “regular” probation. In addition to testing the effects of CAMO as an intermediate treatment, methodological issues, such as level of probation restrictiveness and the effects of prior criminal involvement on probation outcome, are tested. Although the results are mixed, they indicate that level of probation restrictiveness and prior criminal involvement have a greater effect on probation outcome than does CAMO. These findings have ramifications for researchers comparing CAMO probationers to “regular” probationers and for those comparing different CAMO programs.